The use of a mobile educational tool on pressure injury education for individuals living with spinal cord injury/disease: a qualitative research study. Issue 3 (30th January 2022) - Shirai, Takami; Bulandres, Priscilla; Choi, Jee-Ae; D'Ortenzio, David; Moon, Nathan; Musselman, Kristin; Gabison, Sharon
Abstract: Background: As many as 30–60% of individuals living with spinal cord injury/disease (SCI/D) experience at least one pressure injury (PI) in their lifetime. Best practice guidelines in SCI/D rehabilitation emphasize the importance of providing education regarding PI prevention and management for individuals living with SCI/D. Mobile educational applications can be used for PI education however there is limited research on the user-experiences of mobile educational applications about PIs for individuals living with SCI/D. Objectives: The purpose of this study was to explore the experiences of individuals living with SCI/D on the use of Pressure Ulcer Target (PUT), a mobile educational app for PI prevention and management. Methods/Overview: Nine participants living with SCI/D used PUT over two weeks. Individual semi-structured interviews were conducted to explore the participants' perceptions regarding the utility, aesthetics and ease of use of PUT and suggested modifications. A conventional content analysis was used to identify themes and categories from the data. Results: User-experiences with PUT fell into four themes: (1) Strengths and weakness; (2) Target population; (3) Key concepts and messages; and (4) Recommendations for improvement. Conclusions: PUT serves as a review of previously acquired PI knowledge and should be introduced early in rehabilitation to motivate users to prevent PIs. Future studies exploring healthcare professionals' perspectives of PUT are warranted. Implications for rehabilitation: PUT aids individuals living with SCI/D in the community to review PI prevention and management strategies that they learned as inpatients. The use of pictures to deliver patient education regarding PI prevention and management through a mHealth app is recommended. PUT should be introduced early in rehabilitation to motivate users to prevent PIs.